Synthesis Study of Amylum-Carboxymethyl and Amylum-Sulfonate to Increase their Solubility in Water - Khusna Widhyahrini (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2022)
Modified starch is synthesized to change the physical and chemical properties, one of which is solubility. Two new things were produced in the starch substitution process, namely modifications in the final stage (workup) of the reaction of each substituent, namely changes in the neutralization stage/carboxymethyl starch solids using 30% CH3COOH and the use of methanol pro-analyst in the starch sulfonate deposition process. The results of the solubility test showed that at room temperature and a concentration of 1.5% g/L, carboxymethyl substituted starch was completely soluble in water, while starch with the same concentration was completely soluble at 30Â°C. The viscosity test at room temperature resulted in a flow time of 25.02 seconds for starch-carboxymethyl and 10.15 seconds for starch-sulphonate. The a-amylase test was identified by thin layer chromatography (TLC) with the presence of reducing sugar stains on the starch-carboxymethyl hydrolysis product but not on the starch-sulphonate hydrolysis product. The Dinitrosalicylate (DNS) test showed that the amount of reducing sugar of starch sulfonate was much smaller than that of starch-carboxymethyl.